Konsep Ketentraman Hidup Perspektif Quraish Shihab (Studi Surah Al-Insyirah dalam Tafsir Al-Misbah) - Abd Basid; Abd Ghani (Fakultas Syari'ah dan Hukum (FSH) UNSIQ, 2023)
This article is motivated by the worrying reality of human life and requires a deeper understanding in rectifying people's perspectives on achieving prosperity and a peaceful life. This is the reason for the author to re-analyze the concept of a peaceful life which has been linked in the Qur'an and has been elaborated by many mufassir through his works. Especially in Tafsir Al-Misbah by M. Quraish Shihab of surah Al-Insyirah. This surah is well-known as a surah that provides guidance in dealing with various problems in life in general, in fact the sura was revealed regarding the success of the Prophet Muhammad in facing obstacles from infidels, then the ease and ease he obtained after he experienced victory in completing orders from Allah SWT. This study is qualitative in nature, sourced from the literature by using analytical descriptive writing methods. The research analysis uses the Ijmali interpretation method. As a result, the authors suggest to increase faith by getting to know Allah SWT further so that Allah will bestow the welfare that is expected of mankind.